Perspectives of 2022 Islamic Education Students on the Utilization of Canva as a Multimedia Presentation-Based Learning Media - Hidayatullah, Taufiq; Nurussyifa, Nabilla; Sari, Febriani Nurwanda; Anbiya, Bakti Fatwa (Educational Insights, 2024)
This research aims to explore and depict the perspectives of students from the Islamic Education Program (PAI) Class of 2022 regarding the utilization of Canva as a multimedia presentation-based learning tool. In this study, a narrative inquiry method is employed as a qualitative approach to delve into the stories and experiences of students using Canva. The data collection process involves discussions and interviews, which are then analyzed through a narrative analysis approach. The research findings provide significant insights into how students perceive Canva as a multimedia presentation learning tool and to what extent this can enhance the quality of learning in the PAI environment. The implications of the findings support the use of Canva as a potential tool to improve the effectiveness of learning in the digital era. It is expected that this research will make a positive contribution to the development of innovative and engaging learning strategies for students in the PAI Class of 2022.